2015
DOI: 10.1016/j.celrep.2015.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of an Endogenous CXCR4 Antagonist

Abstract: CXCL12-CXCR4 signaling controls multiple physiological processes and its dysregulation is associated with cancers and inflammatory diseases. To discover as-yet-unknown endogenous ligands of CXCR4, we screened a blood-derived peptide library for inhibitors of CXCR4-tropic HIV-1 strains. This approach identified a 16 amino acid fragment of serum albumin as an effective and highly specific CXCR4 antagonist. The endogenous peptide, termed EPI-X4, is evolutionarily conserved and generated from the highly abundant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
264
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(279 citation statements)
references
References 58 publications
15
264
0
Order By: Relevance
“…It is necessary to develop more ubiquitous and effective HIV-1 inhibitor. Up to now, several natural small molecular peptides in human blood and tissues have been identified as HIV-1 entry inhibitors (Munch et al, 2007;Zirafi et al, 2015). However, it is tough to purify and characterize the endogenous antiviral factors circulating in the human body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to develop more ubiquitous and effective HIV-1 inhibitor. Up to now, several natural small molecular peptides in human blood and tissues have been identified as HIV-1 entry inhibitors (Munch et al, 2007;Zirafi et al, 2015). However, it is tough to purify and characterize the endogenous antiviral factors circulating in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…The group of Frank Kirchhoff identified a natural efficient inhibitor of the HIV-1 gp41 fusion peptide named VIRIP through a systematic screening of peptide library generated from human hemofiltrate (Munch et al, 2007). Through screening of hemofiltrate-derived peptide library, this group also discovered another endogenous effective and specific CXCR4 antagonist, a 16 amino acid long fragment of serum albumin, the most abundant protein in human plasma, as an inhibitor of CXCR4-tropic HIV-1 (Zirafi et al, 2015). Moreover, it has been reported that Palmitic acid (PA), which was isolated from Sargassum fusiforme, inhibited HIV entry through interference in gp120-CD4 interaction (Lee et al, 2009;Paskaleva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EPI-X4 has a very short plasma half-life of ~17 min, which may limit its utilization as a therapeutic. However, the identification of several synthetic derivatives, specifically the dimeric derivative designated "WSC02" ((IVRWSKKVPCVS)×2) has been shown to possess superior plasma stability compared to EPI-X4 peptide and exhibited enhanced suppression of HSC migration towards SDF-1 [55]. These promising preliminary studies featuring EPI-X4 and its more stable synthetic derivatives warrant further investigation in their therapeutic potential [59].…”
Section: Novel Modulators Of Cxcr4/sdf-1mentioning
confidence: 99%
“…Intriguingly, while all the prerequisites for the generation of EPI-X4 are ubiquitously available throughout the body, its presence and endogenous regulatory role, if any, on native BM HSC remains to be determined. Nevertheless, EPI-X4 has been demonstrated to reduce basal CXCR4 signalling activity and, therefore, also behaves as an inverse agonist, suggesting endogenous CXCR4 signalling may not be restricted to SDF-1 [55]. Of note, G-CSF induces HSC mobilization through dynamic changes in the BM microenvironment mediated in part by secretion of the proteolytic enzymes cathepsin K or cathepsin G, which are produced by osteoclasts and neutrophils, respectively [51,57,58].…”
Section: Novel Modulators Of Cxcr4/sdf-1mentioning
confidence: 99%
See 1 more Smart Citation